2021
DOI: 10.1002/pat.5285
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pluronic F‐127‐coated ZnO nanoparticles: Synthesis, characterization, and their in‐vitro cytotoxicity evaluation

Abstract: Zinc oxide (ZnO) nanoparticles (NPs) are increasingly recognized for their potential use in various biomedical applications. However, the tendency of bare ZnO NPs to aggregate and their poor stability in the biological environment reduce their biocompatibility and lead to cytotoxicity in normal healthy cells. This study attempted to avoid this by synthesizing a novel Pluronic F-127-coated ZnO NPs and evaluating their cytotoxicity impact on normal healthy human endothelial AE.hy296 cells. The characterization r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…A comparison between IR spectra for F127 and (Eu 4 L 4 )(phen) 4 @F127 was exhibited in the region of 3500–500 cm –1 (Figure b). The high-intensity bands located at 1111 and 844 cm –1 were the stretching vibrations of C–O–C within Pluronic F127 . The peaks at 1283 and 2877 cm –1 were the stretching vibrations of C–H .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A comparison between IR spectra for F127 and (Eu 4 L 4 )(phen) 4 @F127 was exhibited in the region of 3500–500 cm –1 (Figure b). The high-intensity bands located at 1111 and 844 cm –1 were the stretching vibrations of C–O–C within Pluronic F127 . The peaks at 1283 and 2877 cm –1 were the stretching vibrations of C–H .…”
Section: Resultsmentioning
confidence: 96%
“…The high-intensity bands located at 1111 and 844 cm −1 were the stretching vibrations of C−O−C within Pluronic F127. 18 The peaks at 1283 and 2877 cm −1 were the stretching vibrations of C−H. 19 Furthermore, the bands at 956 and 1342 cm −1 were the rock and wagging of CH 2 , respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mateti et al [ 14 ] reported that the size, shape, structure and surface chemistry directly affect BNNs biocompatibility in a dependent manner, showing that lower sizes were less biocompatible on human osteosarcoma cells. Coatings have been shown to present a high effect on the nanomaterials’ biocompatibility [ 15 ], being pluronic, a non-toxic surfactant can significantly improve the biocompatibility and reduce the cytotoxicity of the coated nanomaterials [ 15 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Biocompatibility, non-toxicity, availability, low-cost, UV blocking, antibacterial property, photosensitivity, transparency, and oxidation capacity constitute other merits of ZnO nanoparticles. [29][30][31] Considering the above mentioned literature, to the best of our Filtration was carried out by using a circular electrospun nanofibrous web (diameter = 2.5 cm) supported by a fine stainless mesh (pore size = 74 μm) and secured in a sulfur filtration system consisting of an Erlenmeyer flask (Navigator, USA) and a pump (Castle pumps, UK). Three hundred milliliters of the crude oil was let through the system with a rate of 100 ml h À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatibility, non‐toxicity, availability, low‐cost, UV blocking, antibacterial property, photosensitivity, transparency, and oxidation capacity constitute other merits of ZnO nanoparticles 29–31 …”
Section: Introductionmentioning
confidence: 99%